PERCEPTION OF THE USE OF THE FINANCIAL STATEMENTS SUCCESS AND SMALL COMPANIES PLANTS IN KENDARI (CASE STUDY AT NURI HORTI KENDARI) - Helviani Helviani; Aan Wilhan Juliatmaja (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2016)
This study aimed to determine the perception of the owners and workers of small companies Nuri Horti on the financial statements, to determine the use of the company's financial statements and to determine the success of the company. The location determination is based on the consideration that at this location engaged in agriculture who have received official permission from the local government as a small company of ornamental plants have been designated a Center for Agricultural and Training Governmental (P4S), and the company Nuri Horti has been set up and use financial accounting, although still in a very simple form. The variables observed were: 1) Overview of the company: a brief history of the company, history of owners and labor and of production process. 2) Perception owners and workers about the company's financial statements. 3) The financial statements: Bookkeeping were made by the company and profit (profit) obtained at a certain time. 4) The success of a small company. Analysis of the data used is descriptive measuring devices in the form of Likert scale to measure the perception of respondents, and analysis of Return On Investment (ROI) to measure the ability of the company's capital returns. The results showed that the respondents' perception of the financial statement is very important. A small company Horti Kendari ornamental plants Nuri uses very simple financial statements that are still recording / bookkeeping. The company was successful because it is able to perform a return on capital, and conduct investment activities for the addition / expansion.